Qualities of food - Harvey, Mark, 1943-; McMeekin, Andrew; Warde, Alan (New dynamics of innovation and competition., 2004)
How do people make judgments about what food is worth eating and what tastes good?; how do such judgments come to be shared by groups of people?; what social and organisational processes result in foods being certified as of decent or proper quality?; how.